Concept of the Sense of Control for Wellness Supportive Design - Al Dabbagh, Shamael Mohamed; Bayram, Sarah Alaa (Iraqi Journal of Architecture and Planning, 2018)
Seniors represent an important category in any society being one of the most important institutions of community, Architects, planners, psychologists and sociologists have taken into account major considerations when designing the interior spaces in health institutions to help reinforce a curing environment. The research problem identified by the lack of a clear perception of the concept of sense of control within social support of supportive wellness design theory, in relation to internal space elements and their role in promoting recovery within the atmosphere of the internal environment of the elderly residence, the main hypothesis of the research, which were represented by The elements design of internal spaces that achieve a sense of control within social support contribute in promoting the recovery of elderly residents in care homes.In attempt to find a clear vision a theoretical framework has been set up first, applied then to selected architectural environment in order to verify the hypothesis adopted in this research and to infer the influence of the wellness stimuli hoping to get an ideal architectural design for the future building of seniors living. Where research focused on two models of the theory of reinforcement recovery within the physical environment of the nursing homes :Enhance the way finding system; Enhance control of sensory stimuli systems. The results of the analysis shows the important actors of the internal space elements in promoting recovery within the atmosphere of the internal environments of the senior living. Finally displayed some of the conclusions and recommendations of all. Keywords: Elderly Care Home ØŒ Supportive Design of WellnessØŒ The sense of control, Way Â